Pathogen Genomic Surveillance and Bioinformatics Training and Capacity Development Across Africa - Ms Siddiqah George; Ms Kirsty Lee Garson; Mr Tony Yiquan Li; Mr Perceval Maturure; Professor Nicola Mulder (International Journal of Infectious Diseases)
Introduction: The recent emergence and re-emergence of infectious diseases across Africa have emphasised the critical need for vigorous pathogen genomic surveillance systems on the continent. Effective pathogen genomic surveillance relies heavily on training and capacity development in genomic sequencing and bioinformatics, as rapid public health responses to disease outbreaks depend on the continuous enhancement of these skills. Methods: Over the past four years, we have developed and conducted hybrid training in pathogen genomic surveillance and bioinformatics, for different personas in various national public health institutions across Africa. To date, we have trained over 290 participants from 36 African countries, utilising trainers and facilitators from across the continent to address various competency levels.We have also implemented comprehensive resources to support our training initiatives, including a user-friendly helpdesk ticketing system for ongoing assistance, a robust trainer database for easy access to expert knowledge, and user intuitive websites that host training materials. These tools work jointly to ensure that training and related resources are widely accessible, while also providing participants with support and engagement opportunities long after receiving training. Results: Feedback on our training initiatives, from 75% of participants via post-training evaluation surveys, have underscored the necessity for ongoing efforts in training and capacity building in pathogen genomic surveillance and bioinformatics across the continent. The qualitative feedback emphasised the necessity of further developing improved course materials, sustaining support for participants, and enhancing engagement between trainers and participants. Discussion: Based on our post-training feedback, we are currently consolidating a standardised pathogen genomics surveillance training curriculum to strengthen training and capacity development in Africa. The curriculum is designed to serve as a comprehensive resource for trainers, encompassing content that ranges from foundational courses in generic, wet-lab, and bioinformatics topics to advanced pathogen-specific courses that include tailored genomic surveillance workflows.A future step involves the implementation of more training initiatives across public health institutes in Africa, utilising the standardised pathogen genomics surveillance training curriculum to reinforce training and capacity development. Conclusion: The critical necessity for effective pathogen genomic surveillance systems in Africa has motivated our training and capacity development initiatives in pathogen genomic surveillance and bioinformatics across the continent over the past four years. By maintaining a focus on these training initiatives in the future, Africa's capacity to respond to infectious disease threats can be enhanced, ultimately contributing to the safeguarding of public health throughout the region.